A.03 Cholinergic Neurons in Nucleus Subputaminalis in Primary Progressive Aphasia. (5th June 2019) - Hamodat, H; Fisk, J; Darvesh, S
Abstract : Background: Primary Progressive Aphasia (PPA) involves an isolated impairment of language function at disease onset. The cholinergic system is implicated in language and cholinergic deficits are seen in brains of individuals with PPA. One major source of cholinergic innervation is the nucleus basalis of Meynert (NBM) within which lies the nucleus subputaminalis (NSP). We quantified cholinergic neurons in the NBM and NSP of PPA and controls. Also explored was whether individuals with PPA who subsequently developed different clinical and neuropathological profiles, showed similar cholinergic deficits in the NSP.Methods: Cytoarchitecture of the basal forebrain was studied using Nissl staining in control (n=5) and PPA (n=5) brains. Choline acetyltransferase immunohistochemical staining labelled cholinergic neurons, quantified using Neurolucida software.Results: Compared to matched controls, PPA showed reduction of cholinergic neurons in the NBM, t(4) = 4.224, p = 0.013; Cohen's d=1.89 and the NSP, t(4) = 4.013, p = 0.016; Cohen's d= 1.79. The average percent of cholinergic neuronal loss was higher in the NSP (64.66%) compared to NBM (17.66%).Conclusions: Regardless of underlying pathology, all cases presenting with PPA showed marked loss of cholinergic neurons in the NSP providing further evidence for the importance of this nucleus in language function.